2019
DOI: 10.1186/s12864-019-6198-8
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of pooled genome sequences from Djallonke and Sahelian sheep of Ghana reveals co-localisation of regions of reduced heterozygosity with candidate genes for disease resistance and adaptation to a tropical environment

Abstract: BackgroundThe Djallonke sheep is well adapted to harsh environmental conditions, and is relatively resistant to Haemonchosis and resilient to animal trypanosomiasis. The larger Sahelian sheep, which cohabit the same region, is less well adapted to these disease challenges. Haemonchosis and Trypanosomiasis collectively cost the worldwide animal industry billions of dollars in production losses annually.ResultsHere, we separately sequenced and then pooled according to breed the genomes from five unrelated indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 74 publications
0
13
0
1
Order By: Relevance
“…The four CHIA, CHI3L2, PRDM2 and KDM5B genes that we identified on BTA4 and 16 in the Swedish Red Cattle were previously reported as disease resistance genes (i.e. to gastrointestinal nematodes or bacterial infection) in independent studies on sheep and cattle breeds [96][97][98][99]. In Swedish Red Polled, we found that the TMEM37 gene (BTA2: 71.46-71.66), known to be involved in the resistance to gastrointestinal nematodes, ranked as the closest gene to the most significant SNP showing a signature of selection (q-value = 0.0063).…”
Section: Signatures Of Selection For Disease Resistance Genesmentioning
confidence: 62%
“…The four CHIA, CHI3L2, PRDM2 and KDM5B genes that we identified on BTA4 and 16 in the Swedish Red Cattle were previously reported as disease resistance genes (i.e. to gastrointestinal nematodes or bacterial infection) in independent studies on sheep and cattle breeds [96][97][98][99]. In Swedish Red Polled, we found that the TMEM37 gene (BTA2: 71.46-71.66), known to be involved in the resistance to gastrointestinal nematodes, ranked as the closest gene to the most significant SNP showing a signature of selection (q-value = 0.0063).…”
Section: Signatures Of Selection For Disease Resistance Genesmentioning
confidence: 62%
“…Therefore, it was concluded that the responses of different breeds to the pathogen agent may be different and more studies are needed in the development of breed resistance against diseases (Hadfield et al 2018). In genome sequence analysis of Djallonke and Sahelian sheep resistance to diseases and adaptation to the environment, it was reported that detection of heterozygous diminishing the regions related to these characters may be a sign for selection of economically important diseases (Yaro et al 2019). In our study, it was thought that this study on Akkaraman sheep should be compared in different breeds to determine susceptibility or resistance to different diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies aiming at the ascertainment of the genomic diversity in Djallonké sheep used as reference population Sahel sheep sampled in the same geographical area 42 . Therefore, Burkina-Sahel individuals were used for the XP-EHH analyses.…”
Section: Methodsmentioning
confidence: 99%